Análise do controle motor após treino em esteira com suporte parcial de peso corporal em pacientes com hemiplegia crônica - Abrahão, Fabiana (Universidade Federal de São Carlos, 2005)
Several are the pathologies that induce functional Inbalance, leading to a constant for search for different rehabilitation techniques. One of the most common sequels is the hemiparesia that causes a functional damage, turning the stroke patients one of the principal focuses for the rehabilitation in the area. Therefore the aim of the present research was evaluate the motor control and analyze the increase of the frequency of sessions in the gait training treadmill with body weight support (BWS) in chronic hemiparesis stroke patients. Patients followed an A-B-A design with treadmill training with BWS five times for three weeks (stage A) and treadmill training with BWS three times for three weeks (stage B). The recordings were accomplished in the beginning and in the end of each stage. The collected data were temporal-spatial variables, functional activities through Rivermead test, electromyographics signs of the dorsiflexion and plantar flexion muscular groups of the ankle and electrogoniometry of the dorsiflexion and plantar flexion of the ankle. Eight subjects concluded the experiment. Three patients had better outcomes after 5 times a week treatment, two patients showed improvement only when the treatment was performed 3 times a week, two patients improved gait variables independent of the training frequency and one not improved at all. The analysis of the electromyographics signs and of the data electrogonimetrics didn't allow any relationship with the performance level of the patients. Based on the reslts of the present studies we suggest that, the treadmill training with BWS comes as an effective method for the functional recovery and that it reflects in motor activities that improved activities of daily living. The increase of the frequency of sessions not necessarily reflects in an increase of the motor control, in the largest part of the patients.
Keywords: Funções motoras; Esteira; Marcha; Hemiparesia; Acidente vascular encefálico; Plasticidade neural; Treadmill; Gait; Hemiparesis; Plasticity and stroke; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL